2001
DOI: 10.1016/s0921-4534(01)00399-9
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and magnetic-field-dependent resistivity of MgB2 sintered at high-temperature and high-pressure condition

Abstract: We report the temperature-and magnetic-field-dependent resistivity of MgB2 sintered at high temperature and high pressure condition. The superconducting transition width for the resistivity measurement was about 0.4 K, and the low-field magnetization showed a sharp superconducting transition with a transition width of about 1 K. The resistivity in the normal state roughly followed T 2 behavior with smaller residual resistivity ratio (RRR) of 3 over broad temperature region above 100 K rather than reported T 3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 12 publications
8
35
0
Order By: Relevance
“…Looking at the temperature dependence of Taking the value σ n =5×10 6 Ω -1 m -1 at T c from the dc resistivity measurements on this sample [42] we find that σ 2 (0)= 5×10 8 Ω -1 m -1 and the zero temperature penetration depth is λ L =160…”
Section: Results and Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…Looking at the temperature dependence of Taking the value σ n =5×10 6 Ω -1 m -1 at T c from the dc resistivity measurements on this sample [42] we find that σ 2 (0)= 5×10 8 Ω -1 m -1 and the zero temperature penetration depth is λ L =160…”
Section: Results and Analysismentioning
confidence: 96%
“…The MgB 2 sample was prepared by high pressure (3 GPa) synthesis using commercial MgB 2 powder as described elsewhere [3,42,43]. The sample was sintered at 950 °C and then quenched to room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,7 In addition, the T c and the J c and its dependence on magnetic field are also sample dependent. This sample dependency has been previously attributed to the synthesis conditions (pressure or thermal history), 8 or to the presence of Mg deficiencies or to the presence of oxygen-related defects. 9 Several methods have been reported to obtain well-connected and dense samples, and high-pressure synthesis seems to be able to produce fully dense bulk MgB 2 with electrical transport properties superior to those of sintered samples.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, effect of sintering temperature 500-950 o C at 3 GPa on the superconducting properties of MgB 2 was studied 6) . It was found that as sintering temperature increased, the sample quality was improved, but for the heat treatment above 950 o C the gold started to melt and to adhere strongly to MgB 2.…”
mentioning
confidence: 99%